Residential Segregation and Living Conditions. An Analysis of Social Inequalities in Catalonia from Four Spatial Perspectives - Joan Checa; Oriol Nel·lo (Urban Science, 2021)
Spatial inequalities in living conditions have traditionally been attributed to geographical location, the opposition between urban and rural settings or the size of settlements. Accordingly, the geographical literature has used these oppositions to explain not only differences in access to education, work and services but also diversity of lifestyles, beliefs and even political attitudes. In recent decades, however, urban areas have extended their scope, urbanization has become more dispersed, territories have become more interdependent and spatial hierarchies have tended to weaken. At the same time, social inequalities have become more marked, as manifested spatially by residential segregation. This article puts forward the thesis that residential segregation constitutes a considerably better explanatory factor currently for the elucidation of social inequalities and differences in living conditions in regional spaces than geographical location, the urban/rural divide or the size of settlements. A set of key indicators in the population of residents in Catalonia (level of education, socio-economic position, risk of poverty, self-perceived health and life satisfaction) are therefore analyzed from various spatial perspectives to explore this argument and evaluate each indicator’s explanatory potential. The main results seem to confirm the hypothesis that the most striking spatial inequalities are associated with residential segregation.